2016
DOI: 10.1111/jfpp.13083
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Film Type and Modified Atmosphere Packaging with Different Initial GAS Composition on the Shelf Life of White Mushrooms (Agaricus bisporusL.)

Abstract: The aim of the study was to evaluate the effect of MAP and film thickness on Agaricus bisporus quality. Three initial gas compositions: high oxygen packaging (100% of O2); medium oxygen packaging (50% O2, 50% N2); low oxygen packaging (5% O2, 5% CO2, 90% N2) and two types of polyethylene films of 54 and 39 µm thickness were used. The samples were stored at 4 ± 1C for 14 days. The films and MAP had a significant effect on color and weight loss of the mushrooms. In the case of texture, the gas composition alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Gantner et al () also showed a significant effect ( p < 0.001) of storage time, film thickness and interactions between those factors on lightness ( L *), browning index (BI), weight loss and total color difference in their results of the variance analysis.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Gantner et al () also showed a significant effect ( p < 0.001) of storage time, film thickness and interactions between those factors on lightness ( L *), browning index (BI), weight loss and total color difference in their results of the variance analysis.…”
Section: Resultsmentioning
confidence: 93%
“…The L * parameter at 14 days of storage for all treatments group was above 80, which is assigned as acceptable lightness for consumers. Gantner et al () presented that mushrooms can be classified as a good quality for L * value higher than 86 and fair quality for L * values between 85 and 80. So, in our study after 14 days of storage mushrooms are still be classified as a good quality.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table , the two plastics did not show significant differences for the sensory parameters of dates. Packaging materials may or may not effect on various physico‐chemical properties of fruits and vegetables as they generally act as a barrier to heat, air and other biological and physical factors (Bouzo, Travadelo, & Gariglio, ; Gantner et al, ). The effects of different perforations on sensory characteristics of date fruit was significantly ( p ≤ .05) affected by perforations and relatively better or close to fresh dates sensory properties were observed for H9 treatment (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…D 2 and CD 2 concentrations inside the packages were measured immediately after the mushrooms were packed. D 2 levels in the packages decreased while CD 2 levels increased with the storage time because of the high respiration rate and the gas permeability properties of the PVC film (Gantner et al, 2017). There was no significant difference (p > 0.05) in gas composition values of the packaged mushroom samples.…”
Section: Effect Of Washing With Sc Solution and Packaging On Headspacmentioning
confidence: 88%
“…have been isolated as the most abundant microorganism responsible for the spoilage of mushrooms (Simón & González-Fandos, 2010;Venturini et al, 2011). The shelf-life of mushrooms is very limited, and they lose their commercial value within a few days (Doymaz, 2014b;Gantner et al, 2017). This is a big problem for the distribution and marketing of the fresh mushrooms.…”
Section: Introductionmentioning
confidence: 99%